Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Explanation
[tex]\dfrac{4e^2+16e-9}{2ef+12e-f-6}[/tex]
⇒ First, factor the numerator by grouping:
[tex]=\dfrac{4e^2-2e+18e-9}{2ef+12e-f-6}\\\\\\=\dfrac{2e(2e-1)+9(2e-1)}{2ef+12e-f-6}\\\\\\=\dfrac{(2e+9)(2e-1)}{2ef+12e-f-6}[/tex]
⇒ Now, factor the denominator by grouping:
[tex]=\dfrac{(2e+9)(2e-1)}{2e(f+6)-(f+6)}\\\\\\=\dfrac{(2e+9)(2e-1)}{(2e-1)(f+6)}[/tex]
⇒ We must determine which values of e and f are unacceptable, meaning, will make this expression undefined. These will be the values of e and f that make the denominator equal to 0.
- ⇒ To find these values, let's set each term in the denominator equal to 0, and solve for e and f.
- [tex]2e-1=0[/tex] ⇒ [tex]2e=1[/tex] ⇒ [tex]e=\dfrac{1}{2}[/tex]
- [tex]f+6=0[/tex] ⇒ [tex]f=-6[/tex]
- ⇒ The restrictions for e and f include [tex]e=\dfrac{1}{2}[/tex] and [tex]f=-6[/tex].
[tex]=\dfrac{(2e+9)(2e-1)}{(2e-1)(f+6)}[/tex]
⇒ Reduce values in the numerator and denominator:
[tex]=\dfrac{(2e+9)}{(f+6)}\\\\\\=\dfrac{2e+9}{f+6}[/tex]
Answer
[tex]=\dfrac{2e+9}{f+6}[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.